Efeito da suplementação de isoflavona nos valores de ângulo de fase de mulheres pós-menopausadas - Barbosa, Cinthia Domingos (2017)
Introduction: During postmenopausal period it is observed higher cell damage in women due higher oxidative stress and inflammation comparing with young women, which might reflect in lower phase angle (PhA) values. The consumption of isoflavones may decrease oxidative stress due to antioxidant properties which can probably affect PhA values. Exercise also seems to enhance PhA values, increasing “cell health”. Aim: Therefore, the aim of this study was to evaluate the effect of isoflavone supplementation associated with exercise training on PhA values in postmenopausal women (PW). Methods: A total of 30 post-menopausal women were randomly assigned in a clinical trial, double – blind and controlled study, divided into two groups: one with supplementation of 100mg per day of isoflavone (intervention n = 14) and the other with placebo intake (control n = 16), with combined aerobic and resistance exercise training for 10 weeks. Results: No significant differences were found in anthropometric and dietary parameters in both groups after supplementation. There was improvement in physical function after training protocol (p> 0.001) but not related to isoflavone consumption. There was no change in phase angle values in both groups. (Isoflavone: p = 0.863; Placebo: p = 0.131). Conclusion: Isoflavone supplementation did not change PhA in PW that realized 10 weeks of this exercise protocol. Clinical Trial: NCT03008785.